Penerapan Quality Function Deployment untuk Merancang Rumah Tinggal Generasi Milenial - Lilis Nurhayati; Y.A. Widriyakara Setiadi; Fidelchristo Pijoh; Maria Risky Pratiwi Renwarin (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2026)
The necessity of adequate housing constitutes a fundamental human need. CV Senjaya Makmur, a housing developer in Sidoarjo, faces the challenge of meeting the housing preferences of the millennial generation. The objective of this study is to ascertain the technical attributes required by millennial consumers to inform the design of residential houses. To this end, the Quality Function Deployment (QFD) method will be employed as a framework. The results of the study indicated that the factors considered by millennials include facade color, simple and trendy home design, construction cost, breathing house concept, distance to public facilities, long-term use, efficiency, and flexibility. The highest priorities are the cost of home maintenance (8.513%), the application of easy-care materials (8.494%), and cheap good quality finishing materials (8.329%). Other salient characteristics include optimal furniture arrangement (5.737%), integration of multifunctional spaces (5.508%), and the notion of multi-storey micro-houses (5.453%). These findings offer insights that can inform the design of residential properties to align with the needs and preferences of the millennial generation.Kebutuhan tempat tinggal layak merupakan kebutuhan primer manusia. CV Senjaya Makmur sebagai developer perumahan di Sidoarjo menghadapi tantangan memenuhi preferensi rumah generasi milenial. Penelitian ini bertujuan mengidentifikasi atribut teknis yang dibutuhkan konsumen milenial sebagai acuan perancangan rumah tinggal menggunakan metode Quality Function Deployment (QFD). Hasil penelitian menunjukkan faktor-faktor yang dipertimbangkan milenial meliputi warna fasad, desain rumah simple dan trendy, biaya pembangunan, konsep rumah bernafas, jarak dengan fasilitas publik, penggunaan jangka panjang, efisiensi dan fleksibilitas. Prioritas tertinggi adalah biaya perawatan rumah (8,513%), penerapan material mudah perawatan (8,494%), dan material finishing murah berkualitas baik (8,329%). Karakteristik penting lainnya mencakup penataan furniture yang baik (5,737%), gabungan beberapa fungsi ruang (5,508%), dan konsep rumah mikro bertingkat (5,453%). Temuan ini memberikan masukan bagi pengembang untuk merancang rumah sesuai kebutuhan generasi milenial.